Augustine’s Exegetical Rule for Oneness - Steen, Austin (Augustinian studies, 2024)
This article traces Augustine’s presentation of an exegetical rule for oneness based on scriptural patterns in three different anti-Homoian contexts throughout his life. First, his letter to Pascentius outlines how descriptions of oneness in Scripture that include an added phrase detailing "one what" indicate substantial difference. Pericopes without the additional "one what," though, reveal that the beings are of the same substance. Then, Augustine’s De trinitate builds upon this initial distinction by outlining how Trinitarian unity becomes the soteriological aim for the believers’ oneness with one another. Just as the Father, the Son, and the Spirit are of one substance and of one mind and volition, so too humanity, who is already of one substance, must become of one mind and volition through the same faith. Finally, Augustine’s encounter with Maximinus toward the end of his life elaborates further by explicating the significance of a verb’s singularity or plurality in a biblical verse for substantial oneness. He incorporates an argument that has already appeared in his thought into his approach to oneness in Scripture. This article, therefore, contributes to a greater understanding of Augustine’s exegetical arguments against Homoian theology and the trajectory of his pro-Nicene explanations over his life.